DRONE LAW AND POLICY global development, risks, regulation and insurance. - Tarr, A. A. (Anthony A.); Tarr, Julie-Anne; Thompson, Maurice (Lawyer); Ellis, Jeffrey (Jeffrey John) ([S.l.] : ROUTLEDGE, 2021)
Drone Law and Policy describes the drone industry and its evolution, describing the benefits and risks of its exponential growth. It outlines the current and proposed regulatory framework in Australia, the United States, the United Kingdom and Europe, taking into consideration the current and evolving technological and insurance landscape. This book makes recommendations as to additional regulatory and insurance initiatives which the authors believe are necessary to achieve an effective balance between the various competing interests. The 23 chapters are written by global specialists on crucial topics, such as terrorism and security, airport and aircraft safety, maritime deployment, cyber-risks, regulatory oversight, licensing, standards and insurance. This book will provide authoritative reference and expert guidance for regulators and government agencies, legal practitioners, insurance companies and brokers globally, as well as for major organisations utilising drones in industrial applications.
FOREWORD; A. INTRODUCTION; Chapter 1 New Horizons; B. GLOBAL GROWTH, DEVELOPMENT and APPLICATIONS; Chapter 2 Drones -- Delivering value to the Economy; Chapter 3 Drones -- Healthcare, Humanitarian Efforts and Recreational Use; Chapter 4 Drones and Law Enforcement; Chapter 5 Maritime Uses of Drones; Chapter 6 Urban Environment; C. RISKS; Chapter 7 Global Terrorism and Security; Chapter 8 Aerodromes and Aircraft Safety; Chapter 9 Personal Injury, Property Damage Trespass and Nuisance; Chapter 10 Data protection, Privacy and Big Data; Chapter 11 Cyber-risks; Chapter 12 Product Liability; D. REGULATION; Chapter 13 Regulatory overview; Chapter 14 Transnational Organisations; Chapter 15 National Regulatory Structure and Responses: USA; Chapter 16 National Regulatory Structure and Responses: Spain; Chapter 17 National Regulatory Structure and Responses: United Kingdom; Chapter 18 National Regulatory Structure and Responses: Australia; Chapter 19 Technology Challenges inherent in Safety Regulation; E. INSURANCE; Chapter 20 Insurance: General; Chapter 21 Underwriting Drone Insurance; Chapter 22 Compulsory Third Party Liability Insurance; F. CONCLUSION; Chapter 23 Drones in the future
OCLC-licensed vendor bibliographic record.
Keywords: Drone aircraft -- Law and legislation; TRANSPORTATION / Aviation / General; BUSINESS & ECONOMICS / Industries / Transportation; LAW / Air & Space